Proximal femoral fractures in patients with COVID-19 : Pneumonia and admission from a nursing home are the strongest predictors of mortality - Kohut, Petr; Mezera, Vojtech; Langenhan, Ronny; Reimers, Niklas; Kilper, Anica (Zeitschrift fur Gerontologie und Geriatrie, 2024)
BACKGROUND: Proximal femoral fractures are severe injuries in geriatric patients. Additionally, geriatric patients are at a high risk of death due to coronavirus disease 2019 (COVID-19). OBJECTIVE: To identify predictors of mortality in geriatric patients with COVID-19 and concurrent proximal femoral fractures. MATERIAL AND METHODS: Patients who underwent surgical treatment for proximal femoral fractures and also tested positive for COVID-19 were included. The age, gender, the American Society of Anesthesiology (ASA) score and the admission from a nursing home were considered as variables. The rate of reoperations, the mortality at 3 months and discharge home were evaluated as outcomes. RESULTS: In this study 46 patients with COVID-19 (female/male 31/15, median age 87.0 years with an interquartile range [IQR] of 9.8 years) met the inclusion criteria. Of these, 32 patients (69.6%) had to be cared for in the intensive care unit and 26 patients (56.5%) had a severe course of COVID-19 with pneumonia. The median length of hospital stay for survivors was 19 (IQR 17.5) days and 4 of the patients (8.7%) required surgical revision. The in-hospital and 3‑month mortality were 40.0% (n = 17) and 43.5% (n = 20), respectively. The factors which influenced the in-hospital and 3‑month mortality rates were admission from a nursing home, the presence of pneumonia (increased the risk of death) and female gender (protective). CONCLUSION: The occurrence of COVID-19 in patients with proximal femoral fractures has a high mortality. Admission from a nursing home and the presence of pneumonia increased the risk of death, whereas women were at lower risk.
Keywords: Femoral Fractures; Germany; Female; SARS-CoV-2; fraktury kyčle; ženské pohlaví; mortalita v nemocnicích; Proximal femoral fractures; lidé; fraktury proximálního femuru; Německo; Aged, 80 and over; COVID-19; délka pobytu; Nursing Homes; Length of Stay; Reoperation; Risk Factors; reoperace; retrospektivní studie; Traumatology; Male; fraktury femuru; Aged; Frailty; rizikové faktory; Osteoporotic fractures; Hospital Mortality; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Proximal Femoral Fractures; pečovatelské domovy; Hip Fractures; Humans